2018
DOI: 10.1097/mrr.0000000000000302
|View full text |Cite
|
Sign up to set email alerts
|

Game analysis and clinical use of the Xbox-Kinect for stroke rehabilitation

Abstract: Whole-body movement is required to interact (play) with Microsoft Xbox with the 3D Kinect sensor (Xbox-Kinect) and, therefore, may be suitable for encouraging and practicing movements as part of stroke rehabilitation. We aimed to describe (i) game analysis, (ii) clinical use, and (iii) to characterize the Xbox-Kinect game experience with individuals with chronic stroke. Four therapists played the Xbox-Kinect games and then carried out a games analysis on the basis of the categories suggested by Deutsch. Eleven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
1
14
0
1
Order By: Relevance
“…Authors such as Ho et al [46] suggest that the combination of rehabilitation based on VR and conventional therapy could be more effective for the acquisition of functional improvements in patients after stroke. ese results are supported by systematic reviews [4,44,47] which indicate that VR produces a beneficial effect on ADL when it is used together with conventional approaches, such as in the present study. Along these lines, Gibbons et al [48] indicate that VR interventions are, at least, as effective as conventional physiotherapy for improving the functional results of the lower limbs after a stroke, on the condition that the protocols that are used are made progressively more intensive considering both time and difficulty.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Authors such as Ho et al [46] suggest that the combination of rehabilitation based on VR and conventional therapy could be more effective for the acquisition of functional improvements in patients after stroke. ese results are supported by systematic reviews [4,44,47] which indicate that VR produces a beneficial effect on ADL when it is used together with conventional approaches, such as in the present study. Along these lines, Gibbons et al [48] indicate that VR interventions are, at least, as effective as conventional physiotherapy for improving the functional results of the lower limbs after a stroke, on the condition that the protocols that are used are made progressively more intensive considering both time and difficulty.…”
Section: Discussionsupporting
confidence: 84%
“…e scale used presents the limitation of the lack of validation; however, to our knowledge, no similar tool has quantified these dimensions related to the use of technology in the neurological patient. Other authors [47,59] suggest the need to study the potential acceptability and effectiveness of commercial video games to obtain motivation-related outcomes. In addition, for some authors, the principal characteristics of these interventions are the low cost of the system, its portability, and high levels of acceptance on behalf of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Active video games (AVGs) became available for movement focused rehabilitation when gaming consoles such as the Play Station II (PS2) with the Eye Toy camera, the Nintendo Wii and the Microsoft Xbox with the Kinect camera were trialed by clinicians and tested by researchers [5][6][7]. Analyses of the non-custom AVGs associated with the consoles identified elements of motor learning and therapeutic exercise in order to guide the application of AVGs into physical therapy practice, as well as rehabilitation research [8][9][10][11]. Recent surveys of virtual reality and AVGs confirm that AVGs have become part of the repertoire of rehabilitation tools used for persons poststroke.…”
Section: Introductionmentioning
confidence: 99%
“…Enjoyment is proposed as an important construct to recommend AVG play [25]. It has been measured by the same group of investigators while persons post-stroke: (1) interacted with the PS2 Eye Toy, [5] (2) compared enjoyment while playing the PS2 and the Wii [26] and (3) played Kinect Sports and Adventure games [11]. Across all three studies, enjoyment was reported by persons post-stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decade, the Kinect sensor extensively used for human motion assessment and rehabilitation purposes. Kinect sensor integrated with virtual reality for rehabilitation gaming therapy shows promising results for patient's motor and functional recovery [19][20][21][22][23]. Kinect sensor also used for human upper and lower extremity motion assessment for the purpose of recovery improvement tracking and providing feedback [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%